1997
DOI: 10.1111/j.1399-0039.1997.tb02913.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐C heavy chains free of ß2‐microglobulin: distribution in normal tissues and neoplastic lesions of non‐lymphoid origin and interferon‐γ responsiveness

Abstract: Lacking monospecific antibodies to HLA-C, the expression and synthesis of these molecules have been difficult to evaluate. Using biochemical and flow cytometry approaches, the present report demonstrates that the reactivity of the murine monoclonal antibody L31 is restricted to naturally occurring HLA-C (HLA-Cw1 through -Cw8), HLA-B8 and HLA-B51 heavy chains not associated with beta2-microglobin (beta2m). This is due to two properties of HLA-C heavy chains: (a) they share the L31 epitope which distinguishes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 43 publications
2
53
0
Order By: Relevance
“…The HLA-A, -B, and -C transfectants in 221 were obtained through the courtesy of several investigators (see "Acknowledgments") and are referenced elsewhere (14). Epstein-Barr virus-transformed, HLA-typed, and homozygous B cells are also described elsewhere (12,14).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The HLA-A, -B, and -C transfectants in 221 were obtained through the courtesy of several investigators (see "Acknowledgments") and are referenced elsewhere (14). Epstein-Barr virus-transformed, HLA-typed, and homozygous B cells are also described elsewhere (12,14).…”
Section: Methodsmentioning
confidence: 99%
“…For immunoprecipitation, purified antibodies were covalently linked to Affi-Gel (Bio-Rad). The isoelectric focusing (IEF) and Western blot techniques (reducing conditions in all cases) used have been described (11,12,14). In vitro assembly experiments were performed exactly as described in the presence of the NCPERIITL Cw1 ligand (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulsechase studies have shown that the L31 epitope becomes 'hidden' upon assembly with β 2 m, this process being more efficient in HLA-B than HLA-C heavy chains. HLA-A heavy chains are essentially unreactive with L31 (Setini et al, 1996;Giacomini et al, 1997). HC-10 was raised against denatured HLA-B locus heavy chains and cross-reacts with certain HLA-C and -A products including B8 and A25 (Stam et al, 1986).…”
Section: Immunochemical Methodsmentioning
confidence: 99%
“…The remaining bands in the low (acidic) region of the gel were assigned to HLACw*0701. In contrast to HLA-A and -B alleles (Hajek-Rosenmayr et al, 1989;Setini et al, 1996), HLA-Cw7 displayed a multiplicity of irregularly spaced bands, five of which (marked as Cw7 in (Setini et al, 1996;Giacomini et al, 1997), it does not represent an artifact resulting from plasmid construction or transfection. The nature of this component was not further investigated.…”
Section: Allele Assignment Of Hla-a -B -C Heavy Chain Components Symentioning
confidence: 99%